Peran Diplomasi Panda Tiongkok dalam Kerjasama Konservasi Panda Raksasa di Indonesia - Mayangsari, Safira Mutia; Windiani, Reni; Paramasatya, Satwika (Journal of International Relations, 2021)
Panda diplomacy is one of the soft diplomacy practices carried out by China by lending panda animals to China's partner countries. Panda diplomacy has been carried out since the Tang Dynasty. In Indonesia itself, panda diplomacy began in 2017, when two giant pandas arrived in Indonesia. The arrival of the two giant pandas was the result of the signing of a conservation collaboration between Indonesia and China in 2016. Therefore, this study aims to determine the role of Chinese panda diplomacy in animal conservation collaboration. This study uses a descriptive method with secondary data collection techniques, namely literature studies from text books, journals, news, and internet sources related to this research. The author uses the concept of public diplomacy) to analyze the role of Chinese panda diplomacy towards Indonesia. The results of this study indicate that Panda Diplomacy is one of the methods used by China to strengthen cooperative relations with partner countries, namely Indonesia in the field of conservation and also to strengthen bilateral relations between China and Indonesia in various fields. Panda diplomacy also plays a role in showing Indonesia's image in the international world in the field of giant panda conservation and increasing knowledge regarding the protection of endangered animals.